Cytopenias during Treatment of HIV–HCV-Coinfection with Pegylated Interferon and Ribavirin: Safety Analysis of the OPERA Study. Issue 1 (January 2015) - Pontali, Emanuele; Angeli, Elena; Cattelan, Anna M; Maida, Ivana; Nasta, Paola; Verucchi, Gabriella; Caputo, Antonietta; Iannacone, Claudio; Puoti, Massimo
Background: Until recently, recommendations for HCV treatment in HIV-coinfected patients have been combination therapy with pegylated interferon (PEG-IFN) and ribavirin (RBV). However, this treatment is often accompanied with cytopenias which lead to drug-dose reduction/discontinuation, therefore influencing sustained virological response (SVR). This study aimed at evaluating incidence and predictors of cytopenias and to define their impact on SVR in Italian HIV–HCV-coinfected patients undergoing PEG-IFN/RBV treatment. Methods: OPERA was a multicentric, observational study conducted in 98 Italian centres. Patients with HIV–HCV coinfection were administered with PEG-IFN/RBV combination treatment for 48 weeks. Incidence and time of onset of cytopenias and multiple bone marrow toxicity (mBMT) was monitored. Logistic regression analysis assessed factors associated with SVR, anaemia, neutropenia, thrombocytopenia and mBMT. Results: Between 2005 and 2011, 1, 523 patients were enrolled. Anaemia (haemoglobin <10 g/dl) occurred in 197 (12.9%) patients and a haemoglobin drop ≥3 g/dl was recorded in 796 (52.3%). Anaemia did not impact on SVR, its rate being 42.1% and 38.1%, respectively, in patients with and without anaemia ( P =0.31). Therapy discontinuation due to anaemia occurred in 47 patients (3.1%). Neutropenia (<1, 000 neutrophils/mm 3 ) occurred in 652 (42.8%) patients, and SVR was higher ( P <0.001) for patients with neutropenia (44.8%) compared to without neutropenia (34%). Patients developing neutropenia did not have an increased risk of developing infections. Thrombocytopenia (<100, 000 platelets/mm 3 ) occurred in 595 (39.1%) patients, SVR was not influenced by it (38.2% versus 38.9% in patients with and without thrombocytopenia, respectively; P =0.79), and 16 patients (1.1%) discontinued therapy due to it. Cirrhosis was found in 148/734 evaluated patients (20.2%) and was significantly associated with thrombocytopenia ( P <0.0001). mBMT was found in 417 patients (27.4%). Conclusions: Cytopenias are frequent side effects of PEG-IFN/RBV combination therapy in HIV–HCV-coinfected patients. However, SVR is not negatively affected by their presence, nor is there an increased risk of infections in patients developing neutropenia. Several predicting factors for the onset of cytopenias have been unravelled, which will help to identify early those patients at high risk of developing cytopenia.